HUBUNGAN KOMUNIKASI INTERPERSONAL DAN KOMITMEN TERHADAP ORGANISASI DENGAN KEPUASAN KERJA KARYAWAN PT. PERKEBUNAN NUSANTARA III (PERSERO) - Sarinah, Sarinah; Aziz, Azhar (ANALITIKA, 2010)
This study aims to determine the relationship of interpersonal communication and organizational commitment to employee job satisfaction. The hypothesis in this study were: "There is a positive relationship between organizational commitment interpersonaldan communication with employee job satisfaction". The better interpersonal communication and organizational commitment, the higher the job satisfaction of employees and vice versa worse interpersonal communication and organizational commitment, the lower the job satisfaction of employees.            Research hypothesis was tested by regression analysis two predictors. The analysis shows the price obtained at 14.021 with p F = 0.000, which means there is a very significant positive relationship between interpersonal communication and commitment to the organization by implementing employee job satisfaction on PT. Perkebunan Nusantara III (Persero).            The results showed that the importance to PT. Perkebunan Nusantara III (Persero), to empower employees is based on implementing aspects of interpersonal communication and organizational commitment. It is expected to increase employee job satisfaction in implementing PT. Perkebunan Nusantara III (Persero).